Hair Cell Regeneration - Warchol, Mark E.; Stone, Jennifer S.; Coffin, Allison B.; Popper, Arthur N.; Fay, Richard R. (Cham : Springer International Publishing : Imprint: Springer, 2023)
This volume provides a detailed update on progress in the field of hair cell regeneration with emphasis on more "prospective" views of the various facets of regeneration research. Sensory Regeneration in the Inner Ear: History, Strategies and Prospects Mark E. Warchol, and Jennifer S. Stone Non-mammalian Hair Cell Regeneration: Cellular Mechanisms of Morphological and Functional Recovery Madeleine Hewitt, David W. Raible, and Jennifer S. Stone Cell Junctions and the Mechanics of Hair Cell Regeneration Mark A. Rudolf, and Jeffrey T. Corwin Mammalian Hair Cell Regeneration Ruth Taylor, and Andrew Forge Specification and Plasticity of Mammalian Cochlear Hair Cell Progenitors Melissa M. McGovern, and Andrew K. Groves Inner Ear Cells from Stem Cells - a Path Towards Inner Ear Cell Regeneration Amanda Janesick, Eri Hashino, and Stefan Heller Spiral ganglion neuron regeneration in the cochlea: regeneration of synapses, axons and cells Steven H. Green, Sepand Bafti, Benjamin M. Gansemer, A. Eliot Shearer, Muhammad Taifur Rahman, Mark E. Warchol, and Marlan R. Hansen Genetic and Epigenetic Strategies for Promoting Hair Cell Regeneration in the Mature Mammalian Inner Ear Brandon C. Cox, John V. Brigande, and Bradley J. WaltersDr. Mark Warchol is Professor of Otolaryngology at Washington University School of Medicine in St. Louis. Dr. Jennifer Stone is Research Professor of Otolgaryngolldy/Head and Neck Surgery, University of Washington School of Medicine, Seattle. Dr. Allison Coffin is an Associate Professor in the Department of Integrative Physiology and Neuroscience at Washington State University Vancouver. Dr. Arthur N. Popper is Professor Emeritus and research professor in the Department of Biology at the University of Maryland, College Park. Dr. Richard R. Fay (Deceased) was Distinguished Research Professor of Psychology at Loyola University Chicago.
Sensory Regeneration in the Inner Ear: History, Strategies and Prospects -- Non-mammalian Hair Cell Regeneration: Cellular Mechanisms of Morphological and Functional Recovery -- Cell Junctions and the Mechanics of Hair Cell Regeneration -- Mammalian Hair Cell Regeneration -- Specification and Plasticity of Mammalian Cochlear Hair Cell Progenitors -- Inner Ear Cells from Stem Cells - a Path Towards Inner Ear Cell Regeneration -- Spiral ganglion neuron regeneration in the cochlea: regeneration of synapses, axons and cells -- Genetic and Epigenetic Strategies for Promoting Hair Cell Regeneration in the Mature Mammalian Inner Ear.
Keywords: Neurosciences; Otorhinolaryngology; Neuroscience; Otorhinolaryngology